Rapid sample preparation for detection of antibiotic resistance on a microfluidic disc platform. Issue 3 (4th January 2021) - Perebikovsky, Alexandra; Liu, Yujia; Hwu, Alexander; Kido, Horacio; Shamloo, Ehsan; Song, Dian; Monti, Gabriel; Shoval, Oren; Gussin, Daniel; Madou, Marc
Abstract : We demonstrated a novel instrument and a centrifugal microfluidics disc design that is capable of remarkably accomplishing the sample treatment steps, which pave the way to realize the antibody susceptibility test in point-of-care situation. Abstract : Rapid, point-of-care (PoC) diagnostics for antibiotic susceptibility testing (AST) are critical in combating the antimicrobial resistance epidemic. While new, alternative technologies are capable of rapidly identifying antibiotic resistance, traditional AST methods, where a patient sample is incubated with different antibiotics, remain the most reliable and practical in determining antibiotic effectiveness. Here, we demonstrate a novel sample incubation technique on a microfluidic centrifugal disc (CD) as a proof of concept automated sample processing platform for AST. By using ribosomal RNA (rRNA) as a marker for cell growth, we demonstrated that incubation on the microfluidic CD was enhanced (>1.6 fold) for 11 out of 14 clinically relevant isolates of Escherichia coli compared to traditional shaker incubators. Finally, we utilize the system to identify antibiotic resistance of 11 E. coli isolates incubated with 5 different antibiotics in under 2 hours.